2019
DOI: 10.3389/fmicb.2019.00535
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Specific Prevalence of Hepatitis C Virus NS5A Resistance Associated Substitutions in Mainland China

Abstract: Resistance associated substitutions (RASs) can reduce the efficacy of direct-acting antiviral agents (DAAs) targeting hepatitis C virus (HCV) and lead to treatment failure. Clinical data of HCV NS5A RASs prevalence are limited in China and need to be investigated. A total of 878 unique patient samples with different genotypes (GT) (1b: n = 489, 2a: n = 203, 3a: n = 60, 3b: n = 78, 6a: n = 48) were collected from around mainland China by KingMed Laboratory and analyzed for NS5A RASs distribution by Sanger seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 49 publications
4
24
2
Order By: Relevance
“…Genotype 3, subtype 3b is prevalent in South-East Asia, accounting for 9.7% of cases in a recent study from Thailand 9 and 8.9% in a report from mainland China including 27 provinces or municipalities across the country. 10 In a Chinese single-arm, open-label, phase III trial, 89% of patients infected with subtype 3b without cirrhosis (25/28) and only 50% of those with cirrhosis (7/14 patients) achieved SVR after 12 weeks of sofosbuvir/velpatasvir. 11 Resistance analysis indicated that subtype 3b is inherently resistant to NS5A inhibitors, due to the presence at baseline of the A30K + L31M RAS combination that confers high-level resistance to daclatasvir, elbasvir and velpatasvir and intermediate-level resistance to pibrentasvir.…”
Section: See Article Pages 1099-1105mentioning
confidence: 99%
“…Genotype 3, subtype 3b is prevalent in South-East Asia, accounting for 9.7% of cases in a recent study from Thailand 9 and 8.9% in a report from mainland China including 27 provinces or municipalities across the country. 10 In a Chinese single-arm, open-label, phase III trial, 89% of patients infected with subtype 3b without cirrhosis (25/28) and only 50% of those with cirrhosis (7/14 patients) achieved SVR after 12 weeks of sofosbuvir/velpatasvir. 11 Resistance analysis indicated that subtype 3b is inherently resistant to NS5A inhibitors, due to the presence at baseline of the A30K + L31M RAS combination that confers high-level resistance to daclatasvir, elbasvir and velpatasvir and intermediate-level resistance to pibrentasvir.…”
Section: See Article Pages 1099-1105mentioning
confidence: 99%
“…The proportion of these variants in the treatment-naïve Russian patients infected with the HCV genotypes 1b and 3a (predominant in Russia [12]) was < 5.5%, except for A30S clinical significance of which is limited. Low prevalence of these RASs in the Russian sequence set mirrored their occurrence in treatment naïve patients in the North America, Europe and China [9,31,32]. Thus, while prevalence of RAS in some positions varies geographically [22,31,32], prevalence of polymorphisms in positions 30, 31, and 93 is not subjected to significant geographical variations.…”
Section: Discussionmentioning
confidence: 93%
“…Low prevalence of these RASs in the Russian sequence set mirrored their occurrence in treatment naïve patients in the North America, Europe and China [9,31,32]. Thus, while prevalence of RAS in some positions varies geographically [22,31,32], prevalence of polymorphisms in positions 30, 31, and 93 is not subjected to significant geographical variations. At the same time, the M28V polymorphism in the Russian strains of HCV genotype 1a was found to be unexpectedly frequent (57.9%).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations